Transcriptome-wide analyses of RNA m6A methylation in hexaploid wheat reveal its roles in mRNA translation regulation - Huang, Tao; He, Wei-Jie; Li, Cheng; Zhang, Jing-Bo; Liao, Yu-Cai; Song, Bo; Yang, Peng (Frontiers in Plant Science, 2022)
N6-methyladenosine (m6A) is the most abundant RNA modification in eukaryotic messenger RNAs. m6A was discovered in wheat about 40 years ago, however, its potential roles in the wheat remain unknown. In this study, we profiled m6As in spikelets transcriptome at flowering stages of hexaploid wheat and find that m6As are evenly distributed across A, B and D subgenomes but their extents and locations vary across homeologous genes. m6As is enriched in homeologous genes with close expression levels and the m6A methylated genes are more conserved. The extent of m6A methylation is negatively correlated with mRNA expression levels and its presence on mRNAs have profound impacts on mRNA translation in a location-dependent manner. Specifically, m6As within coding sequences and 3’ UTRs repress the translation of mRNAs while the m6As within 5’UTRs and start codons could promote it. The m6A-containing mRNAs are significantly enriched in processes and pathways of “translation” and “RNA transport”, suggesting the potential role of m6As in regulating the translation of genes involved in translation regulation. Our data also show a stronger translation inhibition by small RNAs (miRNA and phasiRNA) than by m6A methylation and no synergistical effect between the two was observed. We propose a secondary amplification machinery of translation regulation triggered by the changes of m6A methylation status. Taken together, our results suggest translation regulation as a role played by m6As in hexaploid wheat.